2020
DOI: 10.24106/kefdergi.702233
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Umutsuzluk Düzeyleri, Belirsizliğe Tahammülsüzlük ve Özyeterliklerinin İncelenmesi

Abstract: Bu çalışmada üniversite öğrencilerinin yaşadıkları gelecek kaygıları, belirsizliğe tahammülsüzlük, genel özyeterlikleri, ve gelecekte iş bulmaya ilişkin algılarının incelenmesi amaçlanmıştır. Araştırmanın çalışma grubu, Mersin Üniversitesinin çeşitli fakültelerinde öğrenim görmekte olan 636 (336 kadın; 300 erkek) lisans öğrencisinden oluşmaktadır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
(15 reference statements)
1
4
0
Order By: Relevance
“…To the author’s knowledge, no similar studies conducted during the pandemic have found comparable findings. However, prior research supports the present study’s results (Bozkur et al, 2020 ; Hasanshahi et al, 2018 ; Kezer et al, 2016 ; Najafi & Foladjang, 2007 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To the author’s knowledge, no similar studies conducted during the pandemic have found comparable findings. However, prior research supports the present study’s results (Bozkur et al, 2020 ; Hasanshahi et al, 2018 ; Kezer et al, 2016 ; Najafi & Foladjang, 2007 ).…”
Section: Discussionsupporting
confidence: 88%
“…Among the studies conducted during this pandemic, Hacimusalar et al ( 2020 ) similarly found a positive relationship between hopelessness and anxiety, as did Lee ( 2020 ) between hopelessness and COVID-19 anxiety. A significant negative relationship had previously been found between one’s level of hopelessness and general self-efficacy (Bozkur et al, 2020 ; Kezer et al, 2016 ). Moreover, Banerjee ( 2020 ) proposed general self-efficacy belief to be a protective factor against hopelessness during the current pandemic.…”
Section: Present Studymentioning
confidence: 86%
“…Otherwise, the tolerance limit may negatively affect healthy decision-making in personal, social, and cognitive aspects. Erguvan (2015) found a significant correlation between intolerance of uncertainty and psychological well-being.…”
Section: Introductionmentioning
confidence: 83%
“…In the sample of university students, the relationship between intolerance of uncertainty and happiness (Sarıçam, 2014), its relationship with psychological well-being levels (Erguvan, 2015;Geçgin & Sahranç, 2017), its relationship with worry and test anxiety (Sarı & Dağ, 2009;Karataş & Uzun, 2018;Kilit et al, 2020) were examined. In addition, theses were written on intolerance of uncertainty by focusing on the concepts related to the science of psychology (Erguvan, 2015;Armutlu, 2019;Coşkun, 2019), and emotional intelligence, coping with stress (Coşkun, 2019), anxiety (Jenkinson, Milne, & Thompson, 2020), relationships with social anxiety (Wake et al, 2021), emotional disorders (Boswell et al, 2013) were also examined. Additionally, "attitudes toward uncertainty scale" was developed on university students (Ersanlı & Uysal, 2015) as well.…”
Section: Introductionmentioning
confidence: 99%